ТАЛАБАЛАРНИ БИОЛОГИЯДАН ЭЛЕКТРОН РЕСУРСЛАР ЯРАТИШ ВА ФОЙДАЛАНИШГА ТАЙЁРЛАШ ЙЎЛЛАРИ - Эргашева, Г.С. (SCIENCE and SOCIETY, 2017)
The article deals with explores the possibilities of using information and communication technologies in biological education, ways of preparing students to the creation and use of electronic resources. The author of the article gives the contents of the educational telecommunication projects and information about stages of their implementation.
Keywords: information and communication technologies; e-learning; Internet; multimedia resources; means of information and communication technologies; computer; e-mail; website; educational telecommunication project; stages of designing; professional training